An Introduction to Computational Micromechanics - Zohdi, Tarek I.; Wriggers, Peter (Lecture Notes in Applied and Computational Mechanics, 2005)
The recent dramatic increase in computational power available for mathematical modeling and simulation promotes the significant role of modern numerical methods in the analysis of heterogeneous microstructures. In its second corrected printing, this book presents a comprehensive introduction to computational micromechanics, including basic homogenization theory, microstructural optimization and multifield analysis of heterogeneous materials. "An Introduction to Computational Micromechanics" is valuable for researchers, engineers and for use in a first year graduate course for students in the applied sciences, mechanics and mathematics with an interest in the computational micromechanical analysis of new materials.